MINIMIZING PATIENT LENGTH OF STAY IN THE EMERGENCY DEPARTMENT AT ANNA MEDIKA GENERAL HOSPITAL, MADURA - Lumintu, Ida; Rohman, Hidayatur; Annisa, Rullie (Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2024)
Prolonged length of stay (LOS) in emergency departments (EDs) negatively impacts patient care and operational efficiency. This study applies simulation modeling using ARENA software to analyze and optimize ED operations at Anna Medika General Hospital in Madura, Indonesia. Three improvement scenarios were evaluated: adding one nurse, one bed, and one general practitioner. The results show that adding a general practitioner reduced LOS significantly, from 184.64 minutes (3.08 hours) to 154.37 minutes (2.57 hours), making it the most effective intervention. However, the findings emphasize the importance of a holistic approach, as standalone interventions may only address isolated bottlenecks. Combining targeted staffing increases with process optimizations provides the most sustainable improvements. This study highlights simulation’s value in evaluating operational strategies, enabling hospitals to make data-driven decisions that balance cost, resource allocation, and patient satisfaction.